Omega-3 fatty acid-derived resolvins and protectins in inflammation resolution and leukocyte functions: targeting novel lipid mediator pathways in mitigation of acute kidney injury - Hong, Song; Lu, Yan (Frontiers in Immunology, 2013)
Inflammation, in conjunction with leukocytes, plays a key role in most acute kidney injury (AKI). Non-resolving renal inflammation leads to fibrosis and chronic renal failure. Resolvin D series (RvDs) and E series (RvEs), protectins, and maresins are endogenous omega-3 fatty acid-derived lipid mediators (LMs) that potently promote inflammation resolution, by shortening neutrophil life span and promoting macrophage (Mf) nonphelogistic phagocytosis of apoptotic cells and the subsequent exit of Mfs from inflammatory tissue. 14S,21R-dihydroxy docosahexaenoic acid (14S,21R-diHDHA), a Mf-produced autacrine, reprograms Mfs to rescue vascular endothelia. RvD1, RvE1, or 14S,21R-diHDHA also switches Mfs to the phenotype that produces pro-resolving IL-10. RvDs or protectin/neuroprotectin D1 (PD1/NPD1) inhibits neutrophil infiltration into injured kidneys, blocks TLR-mediated inflammatory activation of Mfs, and mitigates renal functions. RvDs also repress renal interstitial fibrosis, and PD1 promotes renoprotective heme-oxygenase-1 expression. These findings provide novel approaches for targeting inflammation resolution and LMs or modulation of LM associated pathways in developing better clinical treatments for AKI.